Self-directed learning practices of TESL postgraduate students in a public Malaysian university / Engku Muhammad Syafiq Engku Safruddin - Engku Safruddin, Engku Muhammad Syafiq (2012)
The development of self-assessment and self-directed learning skills is essential to lifelong learning and becoming effective educators. This case study explores the practices of self-directed learning of TESL postgraduate students. Thiscase study was done in a public Malaysian university involving 59 respondents of TESL postgraduates and 5 TESL postgraduate instructors. The focus of this study has been divided into three areas (information gathering strategies in practicing SDL, challenges in practicing SDL, and role of educators in promoting and facilitating SDL practices among TESL postgraduates). It is found out that the TESL postgraduates utilize multiple resources in gathering information in practicing SDL. Among most used resources are printed books, printed journals, electronic books (EBooks), and Electronic journals (E-Journals). Apart from that, it is also found out that they face some challenges in practicing SDL as adult learners such as having a full schedule and conflicting interests. Through the responses given by both TESL postgraduates and TESL instructors who teach them, it is learnt that majority of the TESL postgraduate students are self-directed in their studies. The findings reveal that self-directed learning is well practiced by postgraduates of the TESL program of a public Malaysian university and they are facilitated by instructors through wellarticulated curriculum, tasks and practices.91.4% of them perceive themselves as autonomous learners and this confirmed by data from their instructors. The study makes the following recommendation. It is hoped that TESL postgraduate students to practice self-directed learning prudently by identifying the challenges and eliminate them in order to optimize their learning opportunities. Apart from that, this study proposes the instructors to be more effective in their practices in facilitating adult learners' learning including working together with the faculty in helping students' learning including tackling plagiarism issues among the students. It is also recommended that the public and institutional libraries to improve their services and increase the facilities so that the students can get as much benefits as possible from it in becoming autonomous learners.